Public Health Services: BPJS Case Study in Indonesia - Yusriadi, Yusriadi (Universitas Medan Area, 2019)
Public services are all forms of service, which are the responsibility and are carried out by the central government and regional governments. One form of innovation in health services is known as the Social Security Organizing Agency (BPJS). BPJS has the goal of realizing the provision of adequate health insurance for each participant and his family members to fulfill the health needs of the Indonesian population. Innovation in health services through the BPJS program shows data on participant health satisfaction levels and satisfaction levels of partner health facilities describing the level of satisfaction of both participants and health facilities have increased. In 2017 the participant satisfaction index was 79.5 percent, while the health facility satisfaction index of 89.5 percent increased compared to 2016 with participant satisfaction at 78.6 percent and health facilities 76.2 percent, strategies to improve the quality of BPJS services through increased collaboration of health facilities, performance-based payments, optimization of roles and functions, developing e-claim management, and enhancing strategic partnerships with stakeholders. Innovations can be started from simplifying regulations, bureaucracy, arranging permits for issuing products that can be a solution for citizens.